Enjoyment of spinning exercise performed in a group session as compared to an individual session - Katrine Trøstrup Beck; Karoline Sofie Lowater; Jan Rafn; Ernst Albin Hansen (Frontiers in Sports and Active Living, 2025)
IntroductionThe degree of perceived enjoyment of performed physical activity may be a key aspect with relevance for the effort to get people to be physically active. Spinning, or indoor cycling, is a widespread physical activity that can be performed in a group or individually. The effect of the group element on the enjoyment of spinning remains unclear. Therefore, the purpose of the present study was to test the hypothesis that enjoyment was greater during spinning exercise performed in a group session as compared to individually.MethodsTwenty recreationally active persons (56 ± 6 years, 1.74 ± 0.09 m, 81.0 ± 14.7 kg, and BMI of 26.5 ± 3.7) performed 44-min group and individual instructor-led spinning sessions. Values of power output, heart rate, and cadence were recorded during the sessions. Perceived enjoyment of the exercise was determined by means of a questionnaire (PACES-8) after the exercise.ResultsValues of power output, heart rate, and cadence were not different between the two sessions. Enjoyment was statistically significantly greater by 1.4 ± 2.1 points (p = 0.005) during spinning performed in a group session as compared to individually. As a reference framework, 56 points is the maximal sum score.ConclusionsThe difference in enjoyment between conditions was modest and clinically insignificant. In other words, the group element of the spinning session was considered to be of minor importance for the participants' perception of enjoyment.